2020
DOI: 10.1098/rsbl.2019.0947
|View full text |Cite
|
Sign up to set email alerts
|

The earliest record of Caribbean frogs: a fossil coquí from Puerto Rico

Abstract: The nearly 200 species of direct-developing frogs in the genus Eleutherodactylus (the Caribbean landfrogs, which include the coquís) comprise an important lineage for understanding the evolution and historical biogeography of the Caribbean. Time-calibrated molecular phylogenies provide indirect evidence for the processes that shaped the modern anuran fauna, but there is little direct evidence from the fossil record of Caribbean frogs about their distributions in the past. We report a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…This find has also raised the critical question of a possible link between these Oligocene Puerto Rican chinchilloids and some of the "giant hutias" (Amblyrhiza Cope, 1868 and Elasmodontomys Anthony, 1916), for which a chinchilloid status is also strongly supported in the framework of that study (Marivaux et al, 2020). Although the pre-Pleistocene evolutionary history of these endemic "giant hutias" remains so far undocumented, lineages of these iconic recently-extinct rodents could have a very great antiquity on the islands, extending back more than 30 million years (as also recently demonstrated for West Indian sloths and coquí frogs; Delsuc et al, 2019;Presslee et al, 2019;Blackburn et al, 2020).…”
Section: Introductionsupporting
confidence: 60%
“…This find has also raised the critical question of a possible link between these Oligocene Puerto Rican chinchilloids and some of the "giant hutias" (Amblyrhiza Cope, 1868 and Elasmodontomys Anthony, 1916), for which a chinchilloid status is also strongly supported in the framework of that study (Marivaux et al, 2020). Although the pre-Pleistocene evolutionary history of these endemic "giant hutias" remains so far undocumented, lineages of these iconic recently-extinct rodents could have a very great antiquity on the islands, extending back more than 30 million years (as also recently demonstrated for West Indian sloths and coquí frogs; Delsuc et al, 2019;Presslee et al, 2019;Blackburn et al, 2020).…”
Section: Introductionsupporting
confidence: 60%
“…Darwin [ 1 ] already recognized that the West Indies (Greater Antilles, Bahamas, and Lesser Antilles) appear to have been colonized by South American terrestrial mammal faunas. By now, paleontological findings of chinchilloid rodents [ 2 , 3 ] and eleutherodactylids [ 4 ] have identified that part of this colonization occurred in late Eocene to early Oligocene times (∼40–30 Ma). This is consistent with relaxed molecular clock constraints from terrestrial faunal elements from the Caribbean such as sloths (recently extinct [ 5 , 6 ]) and spiders [ 7 ], amphibians such as eleutherodactylid frogs and bufonids [ 8 , 9 ], and freshwater aquatic organisms such as cichlids [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…(2018). Fossil data were gathered from Sanchiz (1998), Tietje and Rödel (2018), and Blackburn, Keeffe, Vallejo‐Pareja, and Vélez‐Juarbe (2020). We collected development mode records (whether a species completes metamorphosis within an egg (direct development), has a free‐swimming larval phase (larval development), or completes metamorphosis within the body of the parent (viviparous development)) from secondary references (Lannoo, 2005; Gomez‐Mestre et al., 2012; AmphibiaWeb 2017; IUCN, 2017) and the AmphiBIO database (Oliveira et al., 2017).…”
Section: Methodsmentioning
confidence: 99%